Modeling of reverse water-gas shift reaction in membrane integrated microreactors - İnce, Mert Can. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Synthesis gas (syngas) production by reverse water-gas shift (RWGS) reaction is modeled in a membrane integrated microchannel reactor. Process intensification is performed by in-situ steam separation via a hydrophilic α-Al2O3 supported sodalite membrane (SOD), which allows selective transport of H2O and H2 molecules. CuO/ZnO/Al2O3 (CZA) catalyst is considered as a layer that is washcoated to the inner walls of the rectangular shaped reaction channels of the microreactor. Pure H2, readily available as a reactant, is used as the sweep gas in the permeate channel. Two dimensional, steady–state, isothermal operation of the intensified reactor is quantified by the momentum and mass conservations in the entire flow domain, membrane material transfer and catalytic reaction. The reactor is operated at 523 K, 5-15 bar and inlet molar H2:CO2 ratio = 2-4 and the effects of inlet velocities of the reactive mixture (H2+CO2) and sweep gas (H2), reactor pressure, molar inlet H2:CO2 ratio and flow partitioning on per cent CO2 conversion, amount of CO2 converted and the synthesis gas composition are studied. Membrane assisted efflux of H2O from/ influx of H2 into the reaction channel significantly improves the performance. A non-isothermal study is conducted to demonstrate that the microchannel system has the characteristics of near-isothermal conditions. The effect of flow direction on the reactor operation is found to be negligible. Sweep gas inlet velocity affected the performance metrics significantly. Integration of steam selective membrane and increasing sweep velocity to six times of the reaction channel inlet velocity showed an increase in CO2 conversion from 16.1% to 51.6%. Sizing studies point out that 3.6 m3 multichannel reactor can process H2 input from a 1 MW commercial electrolyzer. The current reactor is also benchmarked with an equivalently operated packed-bed membrane reactor.
Keywords: Microreactors.; Synthesis gas.; Water-gas.